Biodiversity in Enclosed Seas and Artificial Marine Habitats Proceedings of the 39th European Marine Biology Symposium, held in Genoa, Italy, 21-24 July 2004 - Relini, G.; Ryland, J. (Developments in Hydrobiology, 2007)
The main themes of the Symposium were biodiversity in enclosed and semi-enclosed seas and artificial habitats, and the restoration of degraded systems. These themes are highly relevant today both from a basic scientific point of view and from an applied approach. The papers dealing with the first theme represent current research and concerns about marine biodiversity in enclosed seas and will have wide appeal to all those interested in understanding and preserving the biodiversity of the seas and in particular of the Mediterranean and Black Seas. The papers in the second theme represent a synthesis of up-to-date knowledge on artificial habitats and how they can contribute to protection of coastal marine ecosystems, to enhancement of species diversity and biological resources and to restoration of degraded marine environments.